Optimal Design of the Rear Leg Mechanism of Climbing Wheelchair - Li Can; Liu Zengbao; Lu Jianjun; Fan Liubin; Jia Lixiang (Jixie chuandong)
The rear leg mechanism of climbing wheelchair is the typical planar 2 degrees of freedom fivebar linkages,in order to improve the motion performance of the wheelchair,based on the kinematic analysis and the stress analysis on the key point of the rear leg,taking the length of two side links and one linkage of the five bar linkage as the design variable,the mean of the parallel mechanism Jacobian condition number as the objective function,the constraint conditions are given,and the nonlinear genetic algorithm are used to the optimization design of wheelchair rear leg mechanism. After that,the motion track before and after the optimization of five bar mechanism and the stress of the key point are simulated in the MATLAB. Through the comparison shows that,the optimal Jacobian condition number decreases obviously,the active space of five bar mechanism is more compact and the singular configuration of the mechanism is effectively avoided. The position and posture of the rear leg turn more flexible. The force at the key points of the rear leg mechanism is obviously reduced,the noise in the working process is effectively reduced and the wheelchair run more smoothly. In short,through the optimal design,the performance of the wheelchair is significantly improved.